Synergy of Mg2+ and poly(aspartic acid) in additive-controlled calcium carbonate precipitation - Wolf, S.; Jähme, K.; Gebauer, Denis (The Royal Society of Chemistry, 2015)
© The Royal Society of Chemistry.Additive-controlled precipitation of calcium carbonate is central to various fields of research. Technically, scale formation is an important problem, where polycarboxylates are most commonly employed as inhibitors. Herein, we show that the combination of poly(aspartic acid) with magnesium ions leads to synergistic effects that bring about a dramatic increase in the efficiency towards inhibition of nucleation and growth of nanoscopic CaCO3 precursors. These effects can also be crucial in biomineralization processes, where polycarboxylates and magnesium ions are thought to play important roles.